Erlotinib-associated rash in patients with EGFR mutation-positive non-small-cell lung cancer treated in the EURTAC trial. (February 2015) - de Marinis, Filippo; Vergnenegre, Alain; Passaro, Antonio; Dubos-Arvis, Catherine; Carcereny, Enric; Drozdowskyj, Ana; Zeaiter, Ali; Perez-Moreno, Pablo; Rosell, Rafael
ABSTRACT : Aim: This analysis investigates incidence and time course of rash in the EURTAC study.Materials & methods: Patients with EGFR mutation-positive non-small-cell lung cancer were randomized 1:1 to receive once daily erlotinib or 3-weekly cycles of chemotherapy.Results: Of the 86 erlotinib-treated patients, 71 reported rash. Median time to first rash appearance was 0.7 months. Most patients (n = 65) had the same or lower grade rash at final assessment compared with initial assessment. Of the 21 patients with decreased rash grade between initial and final assessments, 61.9% received no erlotinib dose modification, 42.8% had no concomitant rash treatment.Conclusion: Most rash cases were mild, occurred within 1 month of erlotinib treatment, and rapidly improved without the need for erlotinib dose alterations.